Influence of multiple scattering on dynamical effect manifestation in coherent X-ray radiation by relativistic electron - Blazhevich, S.V.; Kolosova, I.V.; Koren’kova, N.A.; Mazilov, A.A.; Noskov, A.V. (Вопросы атомной науки и техники, 2016)
Coherent X-ray radiation by a beam of relativistic electrons crossing a single-crystal plate in Bragg scattering geometry is considered. In the present work, the initial divergence and multiple scattering of electrons on atoms in the target are taken into account. The manifestation possibility of dynamic diffraction effects in the conditions of multiple scattering of electrons in the beam is studied.